The Implementation of The Land Right Transfer Registration According to Letter Citation in Jatibogor Village, Suradadi - Tegal - Ahmad Tsekhudin; Umar Ma'ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
According to the certainty on the material law, the definition of transfer of land right is the transfer of old owner to the new one. There are 2 (two) ways of the transfer of land right, which are to transfer and being transferred. To transfer means the transfer of land right without any legal action done by the owner, for example by the hereditarily. While being transferred refers to the transfer of the land through the legal action by the owner, for example by the purchase and sale. According to Paragraph 37 Article 1 Government Regulation Number 24 the Of 1997, it is stated that the Transfer of land right done by making the deed by Land Titles Registrar, so the transfer deed of land transfer will have a strong proof as a deed in the court system and a deed as the base of issuing the ownership certificate. The registration of the land as Government Regulation Number 24 the Of 1997 aims to give the legal certainty and legal protection to the right holder of the land, apartment units and other registered rights so it can easily prove that himself/herself is the right holder. On the other hand, we also acknowledge the registration of land tax, such as pipil-girik, petok, letter C, which is done by the Tax Office in Java Island. Due to there are still some lands in Indonesia that aren’t registered yet around society.Keywords: The Transfer of A Land Right; Registration; Letter D